Improving Efficiency of Mineral Terminal Performance using Lean Railroading. Issue 11 (November 2019) - Fakoor, Arghavan; Mehranfar, Hamed; Bagheri, Morteza; Ahmadi, Abbas
The purpose of this study is to investigate and identify the waste from the unloading station of mineral cars using the lean thinking approach. In this paper, one of the largest steel producers is investigated as a case study. The time information was collected from the database system of the factory and railway company from April to July 2017. The wastes were identified by using the value stream map, and to reduce the waste, ten solutions have been proposed based on the changes in: (a) operation management; (b) purchase of new equipment; and (c) infrastructure development. Implementation of solutions using the Planimate simulator software shows that the best strategy consists of a combination of three operational management solutions without having to purchase new equipment and without any infrastructure development, which can improve station performance by up to 52% with regards to the total time for the unloading process. In addition, the valuable time of the whole process has been increased from 9 to 19%. This improvement will result in an increase of 21% in the annual turnover of cars to the station destination. As a result, each car annually carries on average 450 tons more freight, in which case the railway's revenues from carrying iron ore would be increased by 24% for this destination.